2021
DOI: 10.3390/biology10100949
|View full text |Cite
|
Sign up to set email alerts
|

Bta-miR-2400 Targets SUMO1 to Affect Yak Preadipocytes Proliferation and Differentiation

Abstract: Yak adipose tissue may have evolved a unique energy metabolism manner to accommodate the organism’s seasonal growth rhythms. MiRNAs regulate multiple biological processes including systemic metabolism and energy homeostasis through post-transcriptional regulations. Rare reports have shown that miRNAs regulate lipid metabolism in domestic yaks. Therefore, we investigated the regulatory mechanisms of bta-miR-2400 in modulating yak preadipocytes proliferation and differentiation. We found that bta-miR-2400 was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Other functional genes revealed in this study were also previously reported to be associated with diverse production traits, including the RCN2 (reticulocalbin 2), PSTPIP1 (proline-serine-threonine phosphatase interacting protein 1), ADRB3 (adrenoceptor beta 3) genes with carcass traits in Hanwoo and Qinchuan cattle [ 35 , 36 ], GABRB3 (gamma-aminobutyric acid type A receptor subunit beta3) and GABRB5 (gamma-aminobutyric acid type A receptor subunit alpha5) genes with temperament in beef cattle [ 37 ], ZNF703 (zinc finger protein 703) and ERLIN2 (ER lipid raft associated 2) genes with average daily gain in Nellore and with residual concentrate intake in Holstein [ 38 ], and GOT1L1 (Glutamic-oxaloacetic transaminase 1 like 1) as a cell indicator of stress in the cattle semen [ 39 ]. Interestingly, we also mapped a microRNA gene of bta-mir-2400 that was experimentally revealed for affecting the preadipocytes proliferation and differentiation in yak [ 40 ], regulating skeletal muscle satellite cells proliferation in Chinese Simmental cattle [ 41 ]. On the whole, the current literature evidence confirms that the revealed significant genomic regions are likely associated with the local environmental adaptations and other production traits in Xieka cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Other functional genes revealed in this study were also previously reported to be associated with diverse production traits, including the RCN2 (reticulocalbin 2), PSTPIP1 (proline-serine-threonine phosphatase interacting protein 1), ADRB3 (adrenoceptor beta 3) genes with carcass traits in Hanwoo and Qinchuan cattle [ 35 , 36 ], GABRB3 (gamma-aminobutyric acid type A receptor subunit beta3) and GABRB5 (gamma-aminobutyric acid type A receptor subunit alpha5) genes with temperament in beef cattle [ 37 ], ZNF703 (zinc finger protein 703) and ERLIN2 (ER lipid raft associated 2) genes with average daily gain in Nellore and with residual concentrate intake in Holstein [ 38 ], and GOT1L1 (Glutamic-oxaloacetic transaminase 1 like 1) as a cell indicator of stress in the cattle semen [ 39 ]. Interestingly, we also mapped a microRNA gene of bta-mir-2400 that was experimentally revealed for affecting the preadipocytes proliferation and differentiation in yak [ 40 ], regulating skeletal muscle satellite cells proliferation in Chinese Simmental cattle [ 41 ]. On the whole, the current literature evidence confirms that the revealed significant genomic regions are likely associated with the local environmental adaptations and other production traits in Xieka cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-26 [ 6 ] and miR-107 [ 7 ] inhibit adipocyte differentiation and adipogenesis by targeting F-box and leucine-rich repeat protein 19 ( FBXL19 ) and cyclin-dependent kinase 6 ( CDK6 ). Alternatively, bta-miR-150 [ 8 ] and bta-miR-2400 [ 9 ] have been determined to promote bovine adipocyte proliferation and inhibit differentiation. Bta-miR-149-5p [ 10 ] and bta-miR-376a [ 11 ] target CREB regulated transcription coactivator ( CRTC ) and KLF transcription factor 15 ( KLF15 ), which inhibits the proliferation and differentiation of bovine adipocytes.…”
Section: Introductionmentioning
confidence: 99%